2022
DOI: 10.3390/genes13111925
|View full text |Cite
|
Sign up to set email alerts
|

Partial Disturbance of Microprocessor Function in Human Stem Cells Carrying a Heterozygous Mutation in the DGCR8 Gene

Abstract: Maturation of microRNAs (miRNAs) begins by the “Microprocessor” complex, containing the Drosha endonuclease and its partner protein, "DiGeorge Syndrome Critical Region 8" (DGCR8). Although the main function of the two proteins is to coordinate the first step of precursor miRNAs formation, several studies revealed their miRNA-independent functions in other RNA-related pathways (e.g., in snoRNA decay) or, for the DGCR8, the role in tissue development. To investigate the specific roles of DGCR8 in various cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…We observed that a third of the miRNAs that are affected by DGCR8 haploinsufficiency are primate-specific and not present in rodents, some of which have been shown to be associated with pluripotency maintenance and self-renewal, including the C19MC cluster (Lin et al , 2010; Mong et al ., 2020). Ree et al has also reported defects in C19MC miRNA processing, despite an inconsistent efficiency in targeting DGCR8 expression in human cells (Reé et al , 2022). The clonal expansion defects observed in DGCR8 HET hESCs could be rescued by reintroducing four independent miRNAs belonging to this cluster, indicating its contribution to proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a third of the miRNAs that are affected by DGCR8 haploinsufficiency are primate-specific and not present in rodents, some of which have been shown to be associated with pluripotency maintenance and self-renewal, including the C19MC cluster (Lin et al , 2010; Mong et al ., 2020). Ree et al has also reported defects in C19MC miRNA processing, despite an inconsistent efficiency in targeting DGCR8 expression in human cells (Reé et al , 2022). The clonal expansion defects observed in DGCR8 HET hESCs could be rescued by reintroducing four independent miRNAs belonging to this cluster, indicating its contribution to proliferation.…”
Section: Discussionmentioning
confidence: 99%